2008
DOI: 10.1213/ane.0b013e318184cfe9
|View full text |Cite
|
Sign up to set email alerts
|

Anemia and Cerebral Outcomes: Many Questions, Fewer Answers

Abstract: A number of clinical studies have associated acute anemia with cerebral injury in perioperative patients. Evidence of such injury has been observed near the currently accepted transfusion threshold (hemoglobin [Hb] concentration, 7-8 g/dL), and well above the threshold for cerebral tissue hypoxia (Hb 3-4 g/dL). However, hypoxic and nonhypoxic mechanisms of anemia-induced cerebral injury have not been clearly elucidated. In addition, protective mechanisms which may minimize cerebral injury during acute anemia h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
83
1
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 170 publications
3
83
1
7
Order By: Relevance
“…Transfusion is necessary to minimize symptoms and risks associated with symptomatic chronic anemia when hemoglobin is at 6 g/dl. Trials of acute normovolemic hemodilution in healthy volunteers and surgical patients found the limit of critical oxygen delivery in humans at about 50 g/l (12,13). Th e goal of early volume replacement is to delay or prevent the chain of events that leads to irreversible shock (13,15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transfusion is necessary to minimize symptoms and risks associated with symptomatic chronic anemia when hemoglobin is at 6 g/dl. Trials of acute normovolemic hemodilution in healthy volunteers and surgical patients found the limit of critical oxygen delivery in humans at about 50 g/l (12,13). Th e goal of early volume replacement is to delay or prevent the chain of events that leads to irreversible shock (13,15).…”
Section: Discussionmentioning
confidence: 99%
“…Rapid respiration and shortness of breath at rest should be considered as disturbing evidence of oxygen defi cit and evidence of cardiac decompensation. Dizziness and fainting are common as anemia progresses, but apprehension, changes in mentation and leg cramps are indications of severe oxygen deprivation and presage coma and death, or course that may lead to organ failure (1,11,12,13). When the amount of blood lost rapidly is equivalent to 30% of the blood volume, a subject may develop oligaemic shock (14).…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly important because of the natural variance in the normal hemoglobin ranges between sexes. The literature describes various plausible mechanisms that explain how anemia could directly contribute to poor outcomes 12. There is a paucity of information, however, investigating the impact of an important clinical factor: whether stroke patients with anemia receive fewer preventative medications pertinent to stroke, such as antiplatelets and anticoagulants (antithrombotics).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, much of the current controversy in this area regarding the role of blood pressure, anemia, and cerebral circulatory physiology in response to specific pharmacologic interventions, e.g., beta blockade, brought to the forefront by the POISE study, would perhaps have been predefined. [53][54][55] Also, a stronger focus would guide the groups to relevant questions, such as: a) What are the parameters of physiologic beta blockade among various types of patients, including age, gender, race, and pharmacogenetics, and how are they influenced by concurrent physiologic processes, e.g., aging, anemia, transfusion, altered loading conditions? Although there is a rich background of literature, only passing consideration has been given to this topic by either group.…”
mentioning
confidence: 99%
“…Ainsi, une grande partie de la controverse dans ce domaine concernant le rôle de la tension artérielle, de l'anémie et de la physiologie circulatoire cérébrale en réaction à des interventions pharmacologiques spécifiques, comme par exemple le bêta-blocage, et mise en exergue par l'étude POISE, aurait peut-être été prédéfinie. [53][54][55] De plus, une direction plus claire aiderait les différents groupes à se concentrer sur des questions pertinentes telles que : a) Quels sont les paramètres du bêta-blocage physiologique chez différents types de patients, y compris l'âge, le sexe, la race et la pharmacogénétique, et comment sont-ils influencés par des processus physiologiques survenant simultanément, comme le vieillissement, l'anémie, la transfusion, des conditions de charge modifiées? Bien que la littérature dans le domaine soit abondante, une attention que très limitée n'a été accordée à ce sujet par l'un et l'autre groupe d'élaboration des directives.…”
unclassified